2019
DOI: 10.1111/are.14388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary levels of essential oil extracts from Moringa oleifera and Artemisia afra on kidney histology, haemato‐immunological parameters and disease resistance in Clarias gariepinus

Abstract: This experiment investigated the effect of dietary supplementation with essential oils from Artemisia afra and Moringa oleifera on haemato‐immunological parameters and resistance in Clarias gariepinus (African Sharptooth catfish) (Burchell, 1822) challenged with Aeromonas hydrophila. The experiment lasted for 45 days. Prior to and postchallenge, white blood cells significantly increased (p < .05) from the 3% to 12% M. oleifera and A. afra supplementation. Pre‐challenge, no significant differences (p > .05) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
3
7
0
2
Order By: Relevance
“…Therefore, it is speculated that dietary Artemisia supplementation improved antioxidant capacity, thereby reduced haemolysis in the HD treatments. Similar to the present results, Mbokane and Moyo (2020) found dietary addition of Moringa oleifera and Artemisia arfa significantly mitigated haemolysis following a bacterial challenge in African sharptooth catfish, Clarias gariepinus , which seems to be related to mitigated oxidative stress induced by the infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is speculated that dietary Artemisia supplementation improved antioxidant capacity, thereby reduced haemolysis in the HD treatments. Similar to the present results, Mbokane and Moyo (2020) found dietary addition of Moringa oleifera and Artemisia arfa significantly mitigated haemolysis following a bacterial challenge in African sharptooth catfish, Clarias gariepinus , which seems to be related to mitigated oxidative stress induced by the infection.…”
Section: Discussionsupporting
confidence: 90%
“…There is no study evaluating the effects of Artemisia on the blood WBC under crowding stress in fish; however, other Artemisia sp. have been beneficial in elevating the blood WBC in African sharptooth catfish (Mbokane & Moyo, 2020) and changing the blood WBC profile in rainbow trout, Oncorhynchus mykiss (Gholamhosseini et al, 2021). The present results demonstrated that Artemisia is capable with preventing/mitigating the adverse effects of high stocking density on the blood leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All that is required is to train farmers to prepare diets containing plant material, injections, and baths. Studies undertaken in South Africa have shown that commonly used medicinal plants, namely, Artemisia afra and Moringa oleifera, improved immunity and disease resistance in Oreochromis mossambicus and C. gariepinus [34,35]. These studies showed that dietary supplementation with these plants improved immunity in C. gariepinus and increased resistance against A. hydrophila, which is one of the most problematic pathogens in catfish culture.…”
Section: Management Of Diseasesmentioning
confidence: 95%
“…Namun penggunaan antibiotik tidak dapat digunakan secara berkelanjutan karena dapat menyebabkan beberapa patogen menjadi resisten. Antibiotik juga dapat bersifat residu pada tubuh ikan (Mbokane dan Moyo, 2019). Salah satu cara yang relatif aman bagi ikan maupun lingkungan dalam mengobati infeksi A. hydrophila adalah dengan menggunakan tanaman sebagai obat herbal sebagai pengganti antibiotik (Tewari et al, 2012;Nahak dan Sahu, 2014).…”
Section: Pendahuluanunclassified
“…Daun kelor memiliki kandungan flavonoid, tanin, saponin, alkaloid, dan terpenoid yang terbukti mampu melawan agen infeksious pada A. hydrophila, serta meningkatkan sistem imun pada ikan (Hammed et al, 2015;Gbadamosi et al, 2016;Rosidah et al, 2018;Mbokane dan Moyo, 2019). Jahe merah bersifat antibakteri dan anti-inflamasi karena memiliki kandungan gingerol, shogaol, zingebren, dan zingeron yang termasuk dalam senyawa fenol.…”
Section: Pendahuluanunclassified